China’s New Exclusionary Rule: An Introduction - Ruihua, Chen (Columbia Journal of Asian Law, 2011)
As early as 1998, China’s Supreme People’s Court (“the SPC”) set forth in one of its Judicial Interpretations a rule reflecting the principle of the “exclusionary rule”: that illegally obtained evidence should be excluded from consideration in criminal trials.’ According to this Judicial Interpretation, oral evidence obtained by investigating personnel by torture, threat, false promise, fraud, and other illegal means cannot be used by a court as the basis for a criminal conviction. But over ten years of judicial practice have made it clear that this principle has not been effectively realized. In June 2010, the SPC, Supreme People’s Procuratorate (“the SPP”), Ministry of Public Security, Ministry of State Security, and Ministry of Justice jointly promulgated the Regulations on the Exclusion of Illegally Obtained Evidence in Criminal Cases (“the Exclusionary Regulations”)’ and Regulations on the Examination and Evaluation of Evidence in Capital Cases (“the Capital Case Regulations”).’ The Exclusionary Regulations establish a system of rules for the exclusion of illegally obtained evidence; the Capital Case Regulations consist mainly of provisions addressing evidentiary rulings in death penalty cases, but several provisions address the exclusion of illegally obtained evidence in particular. The promulgation and implementation of these two documents (collectively, “the Evidence Regulations”), which have the legal force of SPC Judicial Interpretations,’ form a preliminary framework for the exclusionary rule in China.